PERBANDINGAN METODE PELAKSANAAN DINDING PENAHAN TANAH PADA PROYEK UNDERPASS DEWA RUCI MENGGUNAKAN SECANT PILE DAN SHEET PILE - Spetjipto, Jojok Widodo; Suyoso, Hernu; Prakasa, Rony Agung Tri (FSTPT Indonesia, 2015)
Severe traffic congestions are often in Dewa Ruci Intersection. It leads to the Bali Provincial Government is forced to build an underpass at this intersection. The impact of construction will be add to the congestion becomes more severe that will take it during the project. To overcome, it is necessary to make the comparative method that have already used (secant pile) with precast method (sheet pile) is known relatively quickly and cheaply. However, this comparison should be followed up with a risk analysis that will happen with these methods. The results showed that sheet pile can accelerate 13.58 days or 5.21% and reduce Rp. 2,754,284,040.00 or 14.47% of secant pile method. The construction cost risk level of sheet pile is almost equal to secant pile but the construction time risk level of sheet pile is smaller than the secant pile.